OPTIMIZATION OF THE EVALUATION PROCESS OF STUDENTS’ MILITARY PHYSICAL EDUCATION FROM THE COMMAND MASTERʼS DEGREE STUDY PROGRAMS, ORGANIZED BY ”CAROL I” NATIONAL DEFENCE UNIVERSITY - Alin PELMUȘ (Bulletin of "Carol I" National Defense University, 2020)
The article analyzes the evaluation activity in military physical education within the training process, in general, and of the students from the command masterʼs degree study programs, organized by ”Carol I” National Defence University, in particular. Also, during the article, the importance of the evaluation process is noted, and some solutions are presented that can contribute to its optimization.